Letter: Solution‐processed flexible zinc‐tin oxide thin‐film transistors on ultra‐thin polyimide substrates. Issue 4 (22nd April 2016) - Gao, Peixiong; Lan, Linfeng; Xiao, Peng; Lin, Zhenguo; Sun, Sheng; Li, Yuzhi; Song, Wei; Song, Erlong; Zhang, Peng; Luo, Dongxiang; Xu, Miao; Peng, Junbiao
Abstract: In this letter, solution‐processed flexible zinc‐tin oxide (Z0.35 T0.65 O1.7 ) thin‐film transistors with electrochemically oxidized gate insulators (AlOx:Nd) fabricated on ultra‐thin (30 µm) polyimide substrates are presented. The AlOx:Nd insulators exhibited wonderful stability under bending and excellent insulating properties with low leakage current, high dielectric constant, and high breakdown field. The device exhibited a mobility of 3.9 cm 2 /V · s after annealing at 300 °C. In addition, the flexible device was able to maintain the electricity performance under various degrees of bending, which was attributed to the ultra‐thin polyimide substrate. Abstract : A solution‐processed flexible zinc‐tin oxide thin‐film transistor was fabricated on a ultra‐thin polyimide (30µm) substrate with electrochemically oxidized gate insulators (AlOx :Nd), which showed a mobility of 3.9 cm 2 /V·s and was able to maintain the electricity performance under various degrees of bending.